Criminal Act of Embezzlement of Funds and Positions In Foundations for Personal Interests - Muhammad Chaerul Ichsan; Anggriani, Jum (Inovasi Pratama Internasional. Ltd, 2025)
This study examines the phenomenon of criminal acts of fund embezzlement and position abuse in foundations as non-profit organizations in Indonesia. Using normative juridical method with descriptive-analytical approach, the research analyzes characteristics and modus operandi of embezzlement, causative factors, effectiveness of criminal law enforcement, impacts on foundation operations and public trust, and comprehensive prevention strategies. Research findings indicate that inclusion in foundations is generally committed by individuals with direct access to financial management through financial report manipulation, aid fund diversion, and procurement abuse. Main causative factors include weak corporate governance, paternalistic culture, and minimal internal-external oversight. Implementation of criminal law provisions faces obstacles of regulatory overlap, evidence complexity, and verdict inconsistency. Systemic impacts in the form of public trust erosion hinder the philanthropic sector as a whole. Prevention strategies require governance structure improvement, law enforcement coordination enhancement, and technology utilization for fraud detection in maintaining the integrity of Indonesia's philanthropic sector